Pulmonary Talcosis in an Immunocompromised Patient - Thanh-Phuong Nguyen; Sowmya Nanjappa; Manjunath Muddaraju; John N. Greene (Case Reports in Medicine)
The first case of pulmonary talcosis or talc pneumoconiosis related to inhalation of talc during its extraction and processing in mines was described by Thorel in 1896. Pulmonary talcosis is most commonly seen secondary to occupational exposure or intravenous (IV) drug abuse and, occasionally, in excessive use of cosmetic talc. Based on literature review, there has been an increase in reported incidents of pulmonary talcosis due to various forms of exposure to the mineral. We report an 82-year-old man who is diagnosed with Philadelphia chromosome positive pre-B cell acute lymphoblastic leukemia (ALL) treated with palliative imatinib who presented with chronic hemoptysis and dyspnea shortly after his diagnosis. His symptoms were initially thought to be due to an infectious etiology due to his malignancy, immunocompromised state, and radiographic findings until high-resolution computerized tomographic (HRCT) findings showed a diffuse pulmonary fibrosis picture that prompted further questioning and a more thorough history inquiry on his exposure to causative agents of interstitial lung disease. Very often, patients do not recognize their exposure, especially in those whose exposure is unrelated to their occupation. Our case emphasizes the need for thorough and careful history taking of occupational and nonoccupational exposure to known causative agents of interstitial lung disease.